Analiza podobieństwa portfeli inwestycyjnych OFE z wykorzystaniem metod taksonomicznych - Chybalski, Filip (Analysis of the Similarity of Open Pension Funds Portfolios Using Taxonomical Methods, 2007)
The main aim of the article is the analysis of the similarity of open pension funds (OPFs) portfolios. That is the mean to verify the thesis that pension funds realize similar investment strategies. The author uses taxonomical methods in his research, including distance measures and hierarchical trees. In the conclusion the author claims that it is difficult to reject the verified thesis. The differences of open pension funds portfolios are very small. The law regulations concerning investment limits for OPFs cannot be the main reason for this similarity of portfolios because they don't include any limits for the sector structure of shares and this kind of structure is also very similar in case of pension funds in Poland. One may suppose that pension funds create similar portfolios to avoid the situation in which they don't achieve the minimal rate of return and note the shortage of assets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 56-68